The Theory of Reasoned Action and The Prospects of Waqf-Muzar’ah-Supply Chain Model in Zanzibar - Moh'd, Issa Salim (Universitas Muhammadiyah Yogyakarta, 2024)
The contribution of the agricultural sector to the development of Zanzibar Islands is considerable. This very important sector through the clove industry was the economic backbone upon which the government of Zanzibar relied for its foreign exchange and national revenue. However, since 1964, agricultural productivity particularly clove production has continually and significantly decreased due to many problems and challenges, especially financial ones. For example, financial intermediaries including banks, cooperatives and micro-enterprises provide micro-financing to the farmers but with high interest rates along with collateral requirements. The numerous programmes, measures and policies adopted by the relevant parties to find solutions to the dwindling clove production have failed. This study has therefore proposed a Waqf-Muzara’ah- Supply Chain model (WMSCM) to address the challenges. The study has used Theory of Reasoned Action adopt the model. To the model, SPSS, AMOS and SEM have used accordingly. The results show that, both the attitude and subjective norm of the clove farmers in Zanzibar towards using the proposed model are statistically significant and have influence on their behavioral intention in using the model.